The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3989/redc.2018.2.1463
|View full text |Cite
|
Sign up to set email alerts
|

Lo local y lo global de la colaboración científica: ¿qué significa, y cómo visualizarlo y medirlo?

Abstract: Resumen: En un contexto en que hay gran interés en intensificar la colaboración internacional dentro de la práctica científica, este trabajo plantea un acercamiento sobre cómo medir y visualizar el trabajo colaborativo internacional a nivel institucional. Como caso de estudio consideramos las tres áreas del Subsistema de Investigación Científica de la Universidad Nacional Autónoma de México. La información se obtuvo de la base de datos Web of Science, Core Collection y consideramos la producción con participac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
(3 reference statements)
0
2
0
1
Order By: Relevance
“…As indicated by Jung et al [ 42 ], in a context in which there is great interest in intensifying international collaboration within scientific practice, this paper proposes an approach on how to measure and visualize international collaborative work at the institutional level. The low collaboration observed between the different authors in our work contrasts with that found in studies such as by Zhu et al [ 1 ] or Yu et al [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…As indicated by Jung et al [ 42 ], in a context in which there is great interest in intensifying international collaboration within scientific practice, this paper proposes an approach on how to measure and visualize international collaborative work at the institutional level. The low collaboration observed between the different authors in our work contrasts with that found in studies such as by Zhu et al [ 1 ] or Yu et al [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…As Jung et al ( 63 ) show, in a context where there is great interest in intensifying international collaboration within scientific practice, our work aims to present a way to measure and visualize international collaborative work at an institutional level. The remarkable collaboration among the different authors, as observed in our study, is in line with findings from studies such as those by Zhu et al ( 64 ) and Yu et al ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Respecto a la colaboración con países de otras regiones destacan las redes con Estados Unidos, España, China, Francia, entre otros. Estas redes son muy importe para los países latinoamericanos porque en muchos casos le permite acceder a recursos económicos y la transferencia de nuevos conocimientos (Jung, N. & Ruiz-León, A., 2018).…”
Section: Análisis De La Producción Científica Latinoamericana Relacionada a Vehículos Eléctricos En El Contexto Internacionalunclassified